2009
DOI: 10.1016/j.jsha.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of acute rheumatic fever in children: Experience at the children’s hospital, Riyadh, Saudi Arabia

Abstract: ARF continues to occur in Saudi Arabia in the period (1994-2003), despite the progress made in the socio-economic development of the country, and this is often associated with severe cardiac involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
31
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 36 publications
9
31
2
Order By: Relevance
“…[26] In contrast, the frequency of elevated ESR (50.0%) was lower than 94% observed in Saudi Arabia. [28] One child in the present study was noted to have concurrent ARF and post-streptococcal glomerulonephritis, an unusual occurrence that is thought to be due to some GAS strains being both nephritogenic and rheumatogenic. [29] Among the children with ARF, mitral regurgitation was the predominant valve lesion on echocardiography.…”
Section: Discussionmentioning
confidence: 87%
“…[26] In contrast, the frequency of elevated ESR (50.0%) was lower than 94% observed in Saudi Arabia. [28] One child in the present study was noted to have concurrent ARF and post-streptococcal glomerulonephritis, an unusual occurrence that is thought to be due to some GAS strains being both nephritogenic and rheumatogenic. [29] Among the children with ARF, mitral regurgitation was the predominant valve lesion on echocardiography.…”
Section: Discussionmentioning
confidence: 87%
“…The structural similarity between many cardiac tissues and the streptococcal antigen M-Protein activates cytotoxic and humoral immune reaction that damages the heart tissue. Rheumatic heart disease (RHD) is the cardiac manifestations of RF and is associated with inflammation of the valves, myocardium, and/or pericardium [17,18]. Around 3-5% of untreated streptococcal pharyngitis turns into rheumatic fever, most patients are kids 5-15 years old.…”
Section: Rheumatic Fever (Rf)mentioning
confidence: 99%
“…50% of them without previous history of RF [17]. Another study found that RF continue to occur in Saudi Arabia despite the progress made in the socioeconomic development of the country and this is often associated with severe cardiac involvement in 53% of cases [19].…”
Section: Rheumatic Fever (Rf)mentioning
confidence: 99%
See 2 more Smart Citations